Anomaly Detection of ESWT Device Supported by AI Agent Using Phase Portraits of Ballistic Pendulum - Michal SAWICKI (Communications of International Proceedings, 2025)
One of the known physiotherapeutic treatment is extracorporeal shockwave therapy. It lets restore health and the comfort of life. These treatments require the usage of the specialised devices generating shockwave. As each device equipped with mechanical elements it is exposed to defects and operational wear. The objective of the service points repairing these devices is anomaly detection and their repair. Currently the diagnostic of these devices is done in hand and it requires a considerable amount of work. Following the world’s trends in industry with the aim of automation of every process and supporting the AI agents, in this paper the cutting-edge method of measurement of the shockwave energy and AI model that recognises devices were presented.
Keywords: Shockwave; ESWT; Charpy impact test; pendulum; machine learning; time series recognition